Autoimmune hepatitis with abnormally high level of serum alpha-fetoprotein (Clinical case) - A. O. Bueverov; Ye. S. Dolmagambetova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the publication. The case of abnormal elevation of alpha-fetoprotein (AFP) in a patient with autoimmune hepatitis (AIH) of the 1-st type is submitted.Features of clinical case. At a 17 years old female patient AIH of 1-st type debuted by jaundice, severe rise of transaminase activity and level of gamma-globulins. Manifestations of AIH, at first glance were typical, accompanied by over 200-fold elevation of serum concentration of AFP that required differential diagnostics with hepatocellular carcinoma. Achievement of immunosuppressor-induced remission resulted in normalization of AFP level.Conclusion. Derepression of respective gene may serve as the mechanism of serum AFP concentration increase at active hepatitis which, however, in absence of neoplastic proliferation is under control of certain regulatory factors. Over 200-fold elevation of AFP level in presented case, that rapidly decreased up to normal level under the influence of successful immune suppressive treatment, can be hard to explain from traditional point of view. Apparently, it is necessary to take into account specific features of AFP synthesis regulation, manifested at vast destruction of hepatic parenchyma.